A conserved genetic module that encodes the major virion components in both the coliphage T4 and the marine cyanophage S-PM2 - Hambly, Emma (The National Academy of Sciences, 2001)
Sequence analysis of a 10-kb region of the genome of the marine cyanomyovirus S-PM2 reveals a homology to coliphage T4 that extends as a contiguous block from gene (g)18 to g23. The order of the S-PM2 genes in this region is similar to that of T4, but there are insertions and deletions of small ORFs of unknown function. In T4, g18 codes for the tail sheath, g19, the tail tube, g20, the head portal protein, g21, the prohead core protein, g22, a scaffolding protein, and g23, the major capsid protein. Thus, the entire module that determines the structural components of the phage head and contractile tail is conserved between T4 and this cyanophage. The significant differences in the morphology of these phages must reflect the considerable divergence of the amino acid sequence of their homologous virion proteins, which uniformly exceeds 50%. We suggest that their enormous diversity in the sea could be a result of genetic shuffling between disparate phages mediated by such commonly shared modules. These conserved sequences could facilitate genetic exchange by providing partially homologous substrates for recombination between otherwise divergent phage genomes. Such a mechanism would thus expand the pool of phage genes accessible by recombination to all those phages that share common modules.